115k views
3 votes
Simplify.
8c2 + 6c – 2c2 – 5c

Show the process of how it was done.

User Whypee
by
4.5k points

2 Answers

3 votes

Answer:

= 6c2+c

Explanation:

8c2+6c−2c2−5c

=8c2+6c+−2c2+−5c

Combine Like Terms:

=8c2+6c+−2c2+−5c

=(8c2+−2c2)+(6c+−5c)

=6c2+c

User Loosebazooka
by
4.5k points
6 votes

Answer:

6c² - c

Explanation:

Step 1: Write expression

8c² + 6c - 2c² - 5c

Step 2: Combine like terms (c²)

6c² + 6c - 5c

Step 3: Combine like terms (c)

6c² - c

User Quantik
by
4.9k points